Storage duration of autologous stem cell preparations has no impact on hematopoietic recovery after transplantation - Kriegsmann, Katharina; Kriegsmann, Mark; Bruckner, Thomas; Hillengaß, Jens; Goldschmidt, Hartmut; Witzens-Harig, Mathias; Ho, Anthony Dick; Wuchter, Patrick (Biology of blood and marrow transplantation, 2017)
Peripheral blood stem cells (PBSCs) are widely used for autologous blood stem cell transplantation (ABSCT). These cells must be stored for months or even years, usually at temperatures ≤−140°C, until their use. Although several in vitro studies on CD34+ viability and clonogenic assays of PBSCs after long-term storage have been reported, only a few publications have investigated the influence of long-term storage on in vivo hematopoietic reconstitution. In this study, we retrospectively analyzed hematopoietic recovery after storage of PBSCs via controlled-rate freezing (CRF) and cryostorage in 10% DMSO at ≤−140°C in 105 patients with multiple myeloma who received high-dose melphalan before ABSCT. Three groups of PBSC transplantation (n = 247) were delineated based on the storage period: short-term (≤12 months, n = 143), medium-term (>12 and ≤60 months, n = 75), and long-term storage (>60 months, n = 29). A neutrophil increase of ≥.5 × 109/L in medium-term or long-term PBSC cryopreservation groups was observed at day 14 after ABSCT; this increase was comparable to patients who received briefly stored PBSCs (day 15). No negative effect of PBSC storage duration was observed on leucocyte or neutrophil reconstitution. Platelet reconstitutions of ≥20  × 109/L and 50 × 109/L were observed after median times of 10 to 11 and 13 to 14 days after ABSCT, respectively. No influence of PBSC storage duration on platelet recovery of ≥20  × 109/L and ≥50 × 109/L was observed in the 3 storage groups (P = .07, P = .32). The number of previous ABSCTs also had no significant impact upon hematopoietic reconstitution. In conclusion, these results indicate that long-term cryopreservation of PBSC products at vapor nitrogen temperature after CRF does not have a negative effect on hematopoietic recovery even after prolonged storage.